Congestion management Incorporation of FACTS Devices Using Ant Colony Optimization - Prakash Burade (Bulletin of Electrical Engineering and Informatics, 2012)
This paper presents Ant Colony Algorithm (ACA) based approach for the allocation of FACTS (Flexible AC Transmission System) devices for the improvement of Power transfer capacity in an interconnected Power System. The ACA based approach is applied on IEEE 30 BUS System. The system is reactively loaded starting from base to 200% of base load. FACTS devices are installed in the different locations of the power system and system performance is noticed with and without FACTS devices. First, the locations, where the FACTS devices to be placed is determined by calculating active and reactive power flows in the lines. Ant Colony Algorithm is then applied to find the amount of magnitudes of the FACTS devices. This approach of ACA based placement of FACTS devices is tremendous beneficial both in terms of performance and economy is clearly observed from the result obtained.